A Comparative Study of Inorganic and Natural Coagulants for Dairy Wastewater Treatment using Alum Sulphate and Moringa Oleifera - Ravindra Kumar; Vijay Verma; Vimal Kishore; Shobhit Tripathi; Tanvi Singh; Uttkarsh Dubey (International Journal of Pollution: Prevention & Control, 2025)
The treatment of dairy wastewater is essential to reduce its environmental impact, particularly in terms of organic load and suspended solids. This study investigates the application of alum sulphate as an inorganic coagulant for dairy wastewater treatment and compares its effectiveness with the natural coagulant Moringa oleifera. The performance of both coagulants was evaluated based on key water quality parameters, including pH, Biochemical Oxygen Demand (BOD), Total Suspended Solids (TSS), and Total Dissolved Solids (TDS). Experimental procedures involved coagulation-flocculation tests, with alum sulphate solutions prepared and applied under controlled conditions using a JAR Test Flocculator Apparatus. Results indicated that alum sulphate achieved superior reductions in BOD (from 200 mg/L to 60 mg/L) and TSS (from 500-600 mg/L to 200-220 mg/L), demonstrating its high efficiency in removing organic matter and suspended particles. In contrast, Moringa oleifera exhibited greater efficiency in TDS reduction. While alum sulphate is a cost-effective preliminary treatment for dairy wastewater, a multi-stage approach incorporating biological or advanced treatment methods may be necessary for comprehensive wastewater treatment and regulatory compliance. This study highlights the potential of alum sulphate as an effective coagulant while underscoring the need for integrated treatment strategies.
Keywords: Moringa Oleifera; aluminum sulphate; biochemical oxygen demand; inorganic coagulant; wastewater treatment